(untitled) (Iraqi Journal of Medical Sciences, 2024)
Background: Siderophores are crucial for the proliferation of many disease-causing bacteria and also have significant functions in the transportation of non-iron metals, defense against oxidative stress, antibiotic effectiveness, interactions between different species, and the ability to cause disease. Objective: For extraction and purification of siderophores from uropathogenic Escherichia coli (E. coli) standard strain. Methods: Isolation and identification of E. coli was carried out only for urinary tract infection (UTI). Enhancement of the production of siderophores was done by investigating the elements that impact their production. Siderophores were detected by using Chrome azurol S (CAS) assay quantitatively in M9 minimal medium salts 5x. Extraction of siderophores using the Jadhav and Desai (1992) technique. Purification of siderophores by Sephadex LH-20 column and high-performance liquid chromatography (HPLC). Results: A quantitative calculation revealed that 44.6% of siderophores were extracted and purified from uropathogenic E. coli. Conclusion: Uropathogenic E. coli rely heavily on iron uptake or siderophores in the development of UTI in individuals. CAS assay is the most reliable technique for detecting siderophores. Keywords: Siderophore, Sephadex LH-20, HPLC, UPEC, UTI Citation: Jaber RA, Mushrif MH, Al-Mudallal NH. Extraction and purification of siderophores produced by Uropathogenic E. coli local Iraqi virulent strains. Iraqi JMS. 2024; 22(1): 147-153. doi: 10.22578/IJMS.22.1.16